The Phraseological Semantic Field in a Contrastive Linguo-cognitive Study: Directions and Method of Research - Gutovskaya, Marina (Respectus Philologicus, 2014)
This paper presents a contrastive linguo-cognitive study of the phraseological semantic field, here viewed as a means of manifesting the corresponding fragment of the phraseological picture of the world built in consciousness and defined as a semantic unity of phraseological units which are connected with some phenomenon of thereal or imagined world and reveal the phraseological concept of this phenomenon.The paper focuses upon three main aspects of a contrastive linguo-cognitive study of the same phraseological semantic fields in different languages, highlighting their cognitive value: 1)  a semantic inventory of the phraseological semantic field; 2) a phraseological representation of individual phraseological semantic groups as components of the phraseological semantic field and manifestants of separate features of the phraseological concept; and 3) a configuration of the component structure of the phraseological semantic field.  The paper presents a method of contrastive linguo-cognitive study which is carried out in the three mentioned directions and allows explication on the basis of language data, as well as comparison and characterization of the contents of the different languages’ concepts and accents available in these contents. The method emphasizes the need to process language data and the importance of employing statistical procedures, both to estimate the relevance of possible interlanguage differences and to assess the possibility of their interpretation in terms of cognitive and cultural specificity. Use of the method is demonstrated through the example of a contrastive linguo-cognitive study of the Russian and English phraseological semantic field of arguing.
Keywords: Phraseological Semantic Field; Phraseological Concept; Directions and Method of Contrastive Linguo-Cognitive Study of Phraseology